Regulation of subsidies in the civil aircraft industry under the WTO framework - Yang, Kuan (Trinity College (Dublin, Ireland). School of Law, 2016)
The regulation of subsidies has long been an intractable issue in terms of international trade regulation. When it involves the civil aircraft industry, the question of subsidies is even more complex. Conflicts over the use of aircraft subsidies date back to the GATT period and have lingered for decades. As the most important global organisation dealing with trade rules between nations, the WTO has a critical role in dealing with the subsidy problem in the civil aircraft industry. The primary aim of this thesis is to examine whether WTO rules on subsidies are effective in dealing with issues that are unique to the civil aircraft industry. It mainly carries out qualitative research on the application ofthe WTO rules in the sector. The thesis first critically examines the WTO subsidy rules since the GATT period. Then, the characteristics ofthe civil aircraft industry that render subsidy issues in that industry more contentious are discussed. It also investigates the conflicts over the use of aircraft subsidies that have developed since the GATT period. After that, the thesis goes on to assess the rulings of the WTO adjudicating bodies on legal issues regarding the subsidisation of the aircraft sector. This thesis also examines the effectiveness of the WTO’s dispute settlement mechanism in the context of the civil aircraft industry. Although the civil aircraft market has been dominated by the US and the EU, China, amongst others, has entered the sector in a significant way. Thus this thesis pays particular attention to the use of aircraft subsidies in China and their possible legal consequenees under the WTO legal framework.
Keywords: Law, Ph.D.; PhD Trinity College Dublin, 2016